Tutorial of One Dimensional Fourier Transform (DFT) : Theory, Implementation and MATLAB programming - Thakulsukanant, Dr.Kornkamol; Patanavijit, Asst. Prof. Dr.Vorapoj (Journal of Food Health and Bioenvironmental Science, 2019)